'Moving Forward': how health librarians can continue supporting the legacy of Shane Godbolt. (21st December 2020) - Atiogbe, Potenza; Fricker, Alan; Reid, Lucy
Abstract: Over the course of her life, Shane influenced the careers of many people working in health library and knowledge services. This article brings together three personal perspectives exploring aspects of this influence. By considering the activities prompted by contact with Shane, we look to how librarians might build on the example she provided of living a full professional life.